Breast Reconstruction and Adjuvant Therapies - Kronowitz, Steven J. (Thieme Medical Publishers, 2004)
Recent developments in the management of breast cancer have increased the complexity of planning for immediate breast reconstruction. Two recent trials have demonstrated superior locoregional control, disease-free survival, and overall survival in node-positive breast cancer patients with the addition of postmastectomy radiation therapy (XRT) to mastectomy and chemotherapy. On the basis of these results, the use of postmastectomy XRT in patients with early-stage breast cancer is increasing. Unfortunately, it is difficult to predict the presence or extent of axillary lymph node involvement—a major determinant of the need for postmastectomy XRT—before mastectomy. There are two potential problems with performing an immediate breast reconstruction in a patient who will require postmastectomy XRT. First, postmastectomy XRT can adversely affect the aesthetic outcome of an immediate breast reconstruction. Second, an immediate breast reconstruction can interfere with the delivery of postmastectomy XRT. Chemotherapy before or after reconstruction does not significantly increase the occurrence of wound-healing problems and breast reconstruction does not appear to delay the initiation or resumption of chemotherapy. The increasing use of postmastectomy XRT and chemotherapy in patients with early-stage breast cancer necessitates increased communication between the medical oncologist, radiation oncologist, breast surgeon, and plastic surgeon during treatment planning for these patients.